Teachers’ perceptions of ethnomathematics in Sorong Regency, West Papua - Bambang Heriyanto; Heny Sri Astutik (Ethnomathematics Journal, 2021)
The purpose of this study was to describe the knowledge of teachers in Sorong Regency on the concept of ethnomathematical approach, the role of ethnomathematical approach, the implementation of the ethnomathematical approach, the implementation characteristics of ethnomathematical approach, and ethnomathematics knowledge of West Papua. This is qualitative research with qualitative descriptive methods. Data were collected using a questionnaire distributed through Google Form. The study selected several teachers as the research respondents to answer the existing problems in accordance with the research objectives. The results showed that in terms of conceptual knowledge, most teachers had been aware of ethnomathematics and had known the purpose of the ethnomathematical approach, but they had no idea about the principles, advantages, and weaknesses of the ethnomathematical approach. Judging from the role of the ethnomathematical approach, most teachers stated that ethnomathematics helped guide students in their learning, helped students appreciate unexpected useful discoveries, helped them to reflect from their learning and provided them with opportunities to collect information needed to solve math problems, think logically, consistently, systematically, and to take notes carefully. As seen from the implementation of the ethnomathematical approach, most of the teachers had never implemented the ethnomathematical approach in the classroom, and they had no idea about the principles of implementation, ethnomathematical learning strategies, ethnomathematical learning resources, and management of the learning environment in ethnomathematics approach. Based on the implementation characteristics of the ethnomathematical approach, most teachers had no idea about the instruments, content, and cooperation in ethnomathematics learning. Meanwhile, in terms of ethnomathematics knowledge, most of the West Papuan teachers had never heard of the application of ethnomathematical learning using sero kokas, traditional Papuan Tifa tools, Papuan bow and arrow, Papuan noken, and ethnomathematical artifacts from Papua for classroom learning.